A Preliminary Study of The Javan Leopard Behaviour in Meru Betiri National Park - Kholiq, Nur; Sucipto, Adi (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2024)
Meru Betiri National Park (MBNP, 526km2), is one of only three protected areas in east Java that can support a viable Javan leopard population. The Javan leopard has become a priority for management following the extinction of the Javan tiger. Therefore, it is important to know how the Javan Leopard behaves to improve species management. We conducted a field study using camera traps to determine the daily behavior of the Javan leopard in MBNP. A monitoring site was established with 73 stations, with a density of one station per 0.5 x 0.5 km grid cell, providing different but comparable densities and spatial coverage. The results indicate that the Javan leopard displays 9 daily behaviors including walking, observing, standing, cheek rubbing, scraping, urine spraying, claw marking, parenting, vocalizing, and others. Each behavior was observed with a relative frequency of walking (63.25%), observing (14.53%), standing (7.69%), cheek rubbing (5.98%), scraping (4.27%), urine spraying (1.71%), claw marking (0.85%), parenting (0.85%) and vocalizing (0.85%). An analysis of the time spent on each behavior revealed their proportion as follows: walking (382 s, 49.29%), watching (208 s, 26.84%), standing (66 s, 8.52%), cheek rubbing (27 s, 3.48%), scraping (57 s, 7.35%), urine spraying (17 s, 2.19%), vocalizing (9 s, 1.16%), claw marking (4 s, 0.52%) and parenting (5 s, 0.65%).